2017
DOI: 10.1002/mp.12202
|View full text |Cite
|
Sign up to set email alerts
|

A phantom study: Should 124I‐mIBG PET/CT replace 123I‐mIBG SPECT/CT?

Abstract: Purpose: The isotope 123 I is commonly labeled with meta-iodobenzylguanidine (mIBG) for imaging of neuroendocrine tumors, such as pheochromocytomas and neuroblastomas. 123 I-mIBG SPECT/CT imaging is performed for staging, follow-up and selection of patients for treatment with 131 I mIBG. As an alternative to 123 I, 124 I-mIBG PET/CT may be used, potentially taking advantage of the superior PET image quality. The purpose of this study was to investigate whether 124 I PET/ CT improves image quality as compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Image quality was assessed using CNR calculated according to Eq. ():CNR=CSCBσBwhere CS represents the average number of counts in each sphere, CB the average number of counts in the background volumes used to determine the CF, and σB the average standard deviation of the background volumes 15 . The Rose criterion , CNR > 5, was used to classify whether an object is detectable or not 16 .…”
Section: Methodsmentioning
confidence: 99%
“…Image quality was assessed using CNR calculated according to Eq. ():CNR=CSCBσBwhere CS represents the average number of counts in each sphere, CB the average number of counts in the background volumes used to determine the CF, and σB the average standard deviation of the background volumes 15 . The Rose criterion , CNR > 5, was used to classify whether an object is detectable or not 16 .…”
Section: Methodsmentioning
confidence: 99%
“…One approach to improving the quality of nuclear images is therefore to replace SPECT tracers with positron-emitting PET tracers. Examples include the use of diagnostic 124 I-metaiodobenzylguanidine (MIBG) PET instead of 123 I-MIBG SPECT before 131 I-MIBG therapy (51,52) (Fig. 6) or the use of low-abundance internal pair production of 90 Y for 90 Y PET instead of Bremsstrahlung 90 Y SPECT for dosimetry in 90 Y liver radioembolization (Fig.…”
Section: Pet Versus Spectmentioning
confidence: 99%
“…Beijst et al studied the difference in lesion detectability between 131 I-SPECT and 124 I-PET imaging and found that 124 I-PET offers better image quality for similar activity concentrations [8,9].…”
Section: Introductionmentioning
confidence: 99%